2020
DOI: 10.1155/2020/7104806
|View full text |Cite
|
Sign up to set email alerts
|

Acute Bacterial Suppurative Thyroiditis following Fine Needle Aspiration: A Case Report and Review of the Literature

Abstract: Background. Fine needle aspiration (FNA) of thyroid nodules is a simple, reliable, and inexpensive procedure performed on suspicious thyroid nodules found in thyroid ultrasound (US). Acute bacterial suppurative thyroiditis is an uncommon complication of FNA which, however, can be life threatening. Case Presentation. A 49-year-old lady presented with fever and neck pain 1 month after FNA with biochemical evidence of thyrotoxicosis. Repeat US of the thyroid showed interval enlargement of the thyroid nodule, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…It most commonly occurs as a sequela of acute suppurative thyroiditis (AST) which is frequently seen in children with anatomical abnormalities such as a pyriform sinus fistula [2] and thyroglossal duct cyst [3] (tend to present earlier in life) and in adults with pre-existing conditions such as Hashimoto's thyroiditis and thyroid malignancy [1]. Immunocompromised patients and those with a history of trauma such as FNAC and foreign body trauma from esophageal perforation are also at an increased risk of developing AST and thyroid abscess [4][5][6]. Infection may occur via lymphatic or hematogenous spread from distant sites, and organisms isolated include Staphylococcus, Streptococcus (accounting for 70 % of cases) [4], Klebsiella, Salmonella, Mycobacterium, and fungal infections in immunocompromised patients [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It most commonly occurs as a sequela of acute suppurative thyroiditis (AST) which is frequently seen in children with anatomical abnormalities such as a pyriform sinus fistula [2] and thyroglossal duct cyst [3] (tend to present earlier in life) and in adults with pre-existing conditions such as Hashimoto's thyroiditis and thyroid malignancy [1]. Immunocompromised patients and those with a history of trauma such as FNAC and foreign body trauma from esophageal perforation are also at an increased risk of developing AST and thyroid abscess [4][5][6]. Infection may occur via lymphatic or hematogenous spread from distant sites, and organisms isolated include Staphylococcus, Streptococcus (accounting for 70 % of cases) [4], Klebsiella, Salmonella, Mycobacterium, and fungal infections in immunocompromised patients [7].…”
Section: Discussionmentioning
confidence: 99%
“…This patient did not have any congenital anomaly or immunodeficiency conditions. A case report and review of literature published in 2020 by Htet et al shows that around 10 cases of AST have been reported as a complication of FNA [ 5 ]. The existing research indicates that the development of acute bacterial suppurative thyroiditis from FNA can occur within a span of several days to three months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…US is the imaging modality of choice in patients without a compromised airway due to its ability to discriminate the internal anatomy of the gland, and it provides an opportunity for immediate diagnostic and therapeutic aspiration. Thyroid US scans feature in AST include heterogeneous echo-texture of the thyroid gland and development of hypo-to-hyperechoic debris in the thyroid cystic fluid [15]. It is prudent to examine the aspirates and exclude thyroid malignancy that may masquerade as AST.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the uncommon risks of superficial biopsy discussed above, FNA of neck structures includes the rare risk of hematoma of the neck [ 7 ], seeding of cancer along the needle track [ 8 ], and acute bacterial suppurative thyroiditis [ 9 ]. Other risks have been theoretically speculated but have not, to our knowledge, been reported in the literature, including cyst fluid leakage, anaphylactic reaction, pneumothorax, and thromboembolism [ 10 ].…”
Section: Introductionmentioning
confidence: 99%